Questionnaire Survey Medical Futility and Termination of Resuscitation in Out-of-hospital-cardiac-arrest Patients Presenting to Emergency Department in Hospitals in Klang Valley - Nur Aiza Mohamed Salleh; Khadijah Poh; Hafizah Zainal Abidin; Teh Yong Hup Teh (Emergency Physicians Association of Turkey, 2024)
Eurasian Journal of Emergency Medicine (Eurasian J Emerg Med) Volume: 22 Issue: 3 (Page:146-160)